1999
DOI: 10.11150/kansenshogakuzasshi1970.73.25
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Detection Methods for Legionella Species from Environmental Water

Abstract: We investigated selective cultivation media and previous treatments of samples suitable for detection of Legionella species from environmental water and for elimination of co-existing microbes which gave rise to an interference with the evaluation of Legionella sp. growth. Twenty thousand U of polymyxin B (PL-B)/ml and 100 micrograms of oxytetracycline (OTC)/ml seem to be useful as additives to MWY selective agar medium. Both antibiotics markedly inhibited the growth of co-existing microbes with almost no infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Often, pre-enrichment with various inhibitors is needed to eliminate populations of other bacteria (Roberts et al, 1987;Kusnetsov et al, 1994a). Kasuga et al (1999), for example, recently reported that combined pretreatment with acid after heating and the addition of polymyxin B and oxytetracycline into the selective cultivation medium is a useful method for the detection of Legionella sp. from environmental water samples.…”
Section: Detection and Disinfectionmentioning
confidence: 99%
“…Often, pre-enrichment with various inhibitors is needed to eliminate populations of other bacteria (Roberts et al, 1987;Kusnetsov et al, 1994a). Kasuga et al (1999), for example, recently reported that combined pretreatment with acid after heating and the addition of polymyxin B and oxytetracycline into the selective cultivation medium is a useful method for the detection of Legionella sp. from environmental water samples.…”
Section: Detection and Disinfectionmentioning
confidence: 99%
“…Combining these pretreatments is also possible. In this case, heat treatment is performed first, and then samples are cooled to room temperature and treated with acid buffer (Kasuga et al, 1999;Inoue et al, 2014) .…”
Section: Pretreatment Of Concentrated Samplesmentioning
confidence: 99%
“…Swab samples were suspended in 5 ml of 50-fold-diluted PBS. The suspension was then subjected to heat treatment at 50°C for 20 min according to the methods of Kasuga et al [13] followed by acid buffer treatment in HCl-KCl buffer (pH 2·2) for 4 min according to the methods of Bopp et al [14]. The samples were subsequently inoculated onto GVPC agar (Oxoid, Hampshire, UK) plates by the spread plate method, and the plates were incubated at 36°C for at least 7 days.…”
Section: Legionella Detectionmentioning
confidence: 99%